Copper-based composite catalyst as well as preparation method and application thereof
By covering the hydroxyl alumina shell on the inner core of the copper nanowire, the copper-oxy-aluminum metal interface site is constructed, the problem of easy reconstitution of copper-based catalysts is solved, the catalytic performance and stability are improved, and carbon-carbon coupling in carbon dioxide reduction reaction is promoted.
Patent Information
- Application Number
- CN202510666433.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-08-05
AI Technical Summary
Copper-based catalysts are prone to reconstruction in electrocatalytic carbon dioxide reduction reactions, resulting in degradation of catalytic performance and insufficient stability. It is difficult for the prior art to effectively solve the structure and performance relationship of the catalyst.
The hydroxyl alumina shell is coated on the inner core of the copper nanowire, and the copper-oxygen-alumina metal interface site is constructed through Lewis acid-base interaction, which stabilizes the oxidized copper species, inhibits catalyst reconstruction, and improves catalytic performance and stability.
The stability of carbon monoxide intermediates in carbon dioxide reduction reaction is enhanced, carbon-carbon coupling is promoted, catalyst selectivity and stability are improved, and self-reduction of oxidized copper and catalyst deactivation are prevented.
Smart Images

Figure CN120425403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper-based composite catalyst and a preparation method and application thereof. Background Art
[0002] Electrochemical carbon dioxide reduction (ECR) is a promising strategy for converting CO2 into high-value chemicals under mild reaction conditions. A key challenge lies in stabilizing key intermediates to promote carbon-carbon coupling and thereby enhance the selectivity of the C2 product. Among all catalysts, copper exhibits the greatest potential for C2 product formation due to its optimal binding energy with the reaction intermediate.
[0003] However, there are still some problems with current copper-based catalysts under electrocatalytic conditions: (1) Under cathode potential, the instability of metallic copper catalysts makes them prone to dynamic structural evolution and surface reconstruction, which is mainly caused by surface atomic migration or redox reaction, and ultimately leads to a decrease in catalytic performance or catalyst deactivation; (2) The time scale of the reconstruction phenomenon of copper-based catalytic materials is relatively short and has transient characteristics, which makes it difficult to study; (3) The mechanism of catalyst reconstruction is very complex and lacks in-depth understanding and knowledge; (4) Since the catalyst reconstruction phenomenon is easy to occur, it is impossible to distinguish the true structural activity of the catalyst and the relationship between structure and performance.
[0004] At present, the strategy to solve the above problems mainly suppresses the surface atomic migration of copper-based catalysts through the surface restriction effect. The prior art CN118441306A discloses a copper nanowire catalyst with controllable surface oxidation degree, a preparation method and its application. The preparation method is as follows: copper nitrate trihydrate, sodium hydroxide and hydrazine monohydrate are dissolved in deionized water to prepare a solution for use, mixed evenly with ethylenediamine and placed in a water bath for reaction, the obtained precursor is redispersed in different solvents for temperature-raising oxidation, and finally dried to obtain a copper nanowire catalyst with controllable surface oxidation degree. The copper nanowire catalyst synthesized by the prior art with the assistance of different solvents has improved surface roughness, stable structure, controllable oxidation degree, high surface defect density, and also provides a large amount of Cu + However, the structure and performance stability of the catalysts provided by the above-mentioned prior art, as well as the catalytic selectivity, need to be further improved.
[0005] In addition, encapsulation with inorganic capping layers and enhanced metal catalyst-support interactions have been shown to be very effective in stabilizing the catalytic interface, which will affect the charge transfer, structure and interactions around the interface. For copper-based catalysts, studies have shown that the dynamic changes in the oxidized copper species play a key role in achieving high product selectivity. However, the inherent reducibility of the oxidized copper species at cathodic potentials also requires improved stability to prevent the self-reduction of the oxidized copper and subsequent catalyst deactivation.
[0006] Therefore, how to solve the problem that copper-based catalysts are prone to reconstruction, which leads to reduced catalytic performance and decreased stability, has become an urgent problem to be solved. Summary of the Invention
[0007] To address the above-mentioned technical problems, the present invention provides a copper-based composite catalyst, its preparation method, and its application. The copper-based composite catalyst provided by the present invention comprises an aluminum oxyhydroxide shell coated on the surface of a copper nanowire core, which inhibits catalyst reconstruction, stabilizes the copper species in the core, and improves the catalytic performance and stability of the copper-based composite catalyst.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a copper-based composite catalyst, comprising a core and a shell coated on the surface of the core, wherein the core comprises copper nanowires, and the shell comprises aluminum oxyhydroxide.
[0010] The copper-based composite catalyst with a core-shell structure provided by the present invention is a coating of an aluminum oxyhydroxide shell constructed on the surface of a copper nanowire core. The aluminum oxyhydroxide in the shell and the copper nanowire in the core interact with each other through Lewis acid-base to construct a copper-oxygen-aluminum metal interface site on the surface of the core, which can promote the interaction of charge transfer, improve the interaction between the surface copper atoms and the main copper, and at the same time, stabilize the oxidized copper species in the core and avoid the reconstruction of the copper-based catalyst. Thus, during the electrocatalytic carbon dioxide reduction reaction, the self-reduction of the oxidized copper at the cathode and the deactivation of the catalyst can be prevented. In addition, the improvement of the stability of the copper-based composite catalyst can enhance the stability of the carbon monoxide intermediate generated during the carbon dioxide reduction reaction, thereby promoting carbon-carbon coupling and improving the catalytic performance of the copper-based composite catalyst.
[0011] Preferably, the shell has a mesoporous structure.
[0012] The present invention adopts a shell with a mesoporous structure, and its specific structure is a mesoporous structure that is circuitous from the inside to the outside, which can regulate the interaction force between aluminum oxyhydroxide and copper atoms in the core and electron transfer.
[0013] Preferably, the average pore size of the mesoporous structure in the shell is 2-4 nm, for example, 2 nm, 2.5 nm, 3 nm, 3.5 nm or 4 nm.
[0014] Preferably, the average thickness of the shell is 2-7 nm, for example, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, 5.5 nm, 6.0 nm, 6.5 nm or 7.0 nm.
[0015] Preferably, the specific surface area of the copper-based composite catalyst is 40-80m 2 / g, for example 40m 2 / g、45m 2 / g, 50m 2 / g、55m 2 / g, 60m 2 / g、65m 2 / g、70m 2 / g、75m 2 / g or 80m 2 / g, etc.
[0016] Preferably, in the copper-based composite catalyst, the molar ratio of the copper element in the copper nanowires to the aluminum element in the aluminum oxyhydroxide is 1:(0.006-0.03), for example, 1:0.006, 1:0.008, 1:0.010, 1:0.012, 1:0.014, 1:0.016, 1:0.018, 1:0.020, 1:0.022, 1:0.024, 1:0.026, 1:0.028 or 1:0.030, etc.
[0017] Preferably, the copper element in the copper nanowires includes divalent copper and monovalent copper.
[0018] The copper-based catalyst provided by the present invention comprises copper in the copper nanowires of the inner core including divalent copper and monovalent copper, wherein the divalent copper exists in the form of cupric oxide and the monovalent copper exists in the form of metastable cuprous oxide, which forms a copper-oxygen-aluminum interface site with the aluminum element in the shell to stabilize the metastable cuprous oxide. While ensuring the realization of a highly selective carbon dioxide reduction reaction product, the self-reduction of the oxidized copper is prevented and the stability of the copper-based composite catalyst is improved.
[0019] Preferably, the molar ratio of the divalent copper to the monovalent copper is (7-9):(1-3), for example, 7.0:3.0, 7.5:2.5, 8.0:2.0, 8.5:1.5 or 9.0:1.0.
[0020] Preferably, the average diameter of the copper nanowires is 30-70 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm or 70 nm.
[0021] Preferably, the average length of the copper nanowires is 1-100 μm, for example, 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.
[0022] In a second aspect, the present invention provides a method for preparing the copper-based composite catalyst according to the first aspect, the preparation method comprising the following steps:
[0023] A first organic solvent containing copper nanowires, a second organic solvent containing water, and a third organic solvent containing an acidic reagent are first mixed to obtain a first mixed product; the first mixed product is second mixed with a fourth organic solvent containing an organic aluminum compound, separated, and then dried to obtain the copper-based composite catalyst.
[0024] The present invention provides a method for preparing a copper-based composite catalyst. The method comprises the following steps: mixing copper nanowires with water, an acidic reagent, and an organoaluminum compound; wherein the organoaluminum compound is hydrolyzed upon contact with water; and simultaneously, an organic solvent is used to dilute the water content and the content of the organoaluminum compound in the mixture, thereby regulating the speed of the hydrolysis process, thereby forming a coating shell of an aluminum hydroxy compound of a specific composition on the surface of the copper nanowires. The addition of acetic acid can regulate the microstructure of the shell, thereby forming a hydroxyaluminum shell having a mesoporous structure. The use of a third organic solvent can dilute the content of acetic acid, thereby further optimizing the shell microstructure, regulating the crystal structure of the shell and the pore structure of the hydroxyaluminum shell, and improving the stabilization effect of the shell protective layer.
[0025] In the preparation method provided by the present invention, the first organic solvent, the second organic solvent, the third organic solvent and the fourth organic solvent do not participate in the reaction, but only provide reaction media and are used to dilute the concentration of added substances, thereby controlling the progress of the reaction.
[0026] Preferably, in the first organic solvent containing copper nanowires, the mass volume ratio of the copper nanowires to the first organic solvent is 0.3-1 mg / mL, for example, 0.30 mg / mL, 0.35 mg / mL, 0.40 mg / mL, 0.45 mg / mL, 0.50 mg / mL, 0.55 mg / mL, 0.60 mg / mL, 0.65 mg / mL, 0.70 mg / mL, 0.75 mg / mL, 0.80 mg / mL, 0.85 mg / mL, 0.90 mg / mL, 0.95 mg / mL or 1.00 mg / mL, etc.
[0027] Preferably, the preparation process of the first organic solvent containing copper nanowires comprises: dispersing the copper nanowires in the first organic solvent, and subjecting the solvent to ultrasound to obtain the first organic solvent containing copper nanowires.
[0028] Preferably, the copper nanowires are pretreated before being dispersed in the first organic solvent.
[0029] Preferably, the pretreatment method includes cleaning.
[0030] The present invention adopts an organic solvent to perform a pretreatment process of multiple centrifugal washing on the copper nanowires, wherein the organic solvent used for washing the copper nanowires includes but is not limited to ethanol, and the number of centrifugal washings is more than 2 times.
[0031] Preferably, in the second organic solvent containing water, the volume ratio of the second organic solvent to the water is 1:(0.004-0.012), for example, 1:0.004, 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009, 1:0.010, 1:0.011 or 1:0.012, etc.
[0032] Preferably, the preparation process of the third organic solvent containing the acidic reagent comprises: diluting the acidic reagent with a third organic solvent to obtain the third organic solvent containing the acidic reagent.
[0033] Preferably, the concentration of the acidic reagent before dilution is 10-17.4 mol / L, such as 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L, 16 mol / L, 17 mol / L or 17.4 mol / L.
[0034] Preferably, the acidic reagent comprises acetic acid.
[0035] Preferably, in the third organic solvent containing the acidic reagent, the volume ratio of the third organic solvent to the acidic reagent is 1:(0.0004-0.012), for example, 1:0.0004, 1:0.001, 1:0.002, 1:0.004, 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009, 1:0.010, 1:0.011 or 1:0.012, etc.
[0036] Preferably, in the first mixed product, the mass volume ratio of the copper nanowires to the water is (2-9.5)×10 4 mg / mL, for example 2.0×10 4 mg / mL, 3.0×104 mg / mL, 4.0×10 4 mg / mL, 5.0×10 4 mg / mL, 6.0×10 4 mg / mL, 7.0×10 4 mg / mL, 8.0×10 4 mg / mL, 9.0×10 4 mg / mL or 9.5×10 4 mg / mL, etc.
[0037] Preferably, in the first mixed product, the volume ratio of the water to the acidic reagent is 1:(0.01-0.7), for example, 1:0.01, 1:0.05, 1:0.10, 1:0.15, 1:0.20, 1:0.25, 1:0.30, 1:0.35, 1:0.40, 1:0.45, 1:0.50, 1:0.55, 1:0.60, 1:0.65 or 1:0.70, etc.
[0038] Preferably, in the fourth organic solvent containing the organoaluminum compound, the concentration of the organoaluminum compound is 20-30 mmol / L, for example, 20 mmol / L, 22 mmol / L, 24 mmol / L, 26 mmol / L, 28 mmol / L or 30 mmol / L.
[0039] Preferably, in the second mixing process, the molar ratio of the copper element in the copper nanowires to the aluminum element in the organic aluminum compound is 1:(0.006-0.03), for example, 1:0.006, 1:0.008, 1:0.010, 1:0.012, 1:0.014, 1:0.016, 1:0.018, 1:0.020, 1:0.022, 1:0.024, 1:0.026, 1:0.028 or 1:0.030, etc.
[0040] Preferably, the first organic solvent, the second organic solvent, the third organic solvent and the fourth organic solvent independently comprise isopropyl alcohol.
[0041] Preferably, the temperature of the second mixing is 50-80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0042] Preferably, the second mixing time is 15-25 hours, for example, 15 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours or 25 hours.
[0043] Preferably, the separation method includes centrifugation.
[0044] Preferably, the centrifugal rotation speed is 3000-4000 rpm, such as 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm or 4000 rpm.
[0045] Preferably, the centrifugation time is 3-10 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0046] Preferably, the separated solid product is washed after the separation.
[0047] Preferably, the washing agent comprises ethanol.
[0048] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0049] (1) Dispersing copper nanowires in a first organic solvent at a mass-to-volume ratio of 0.3-1.0 mg / mL, and ultrasonically obtaining a first organic solvent containing copper nanowires.
[0050] According to the volume ratio of the second organic solvent to water being 1:(0.004-0.012), the water is diluted with the second organic solvent to obtain a second organic solvent containing water.
[0051] According to the volume ratio of the third organic solvent to the acidic reagent being 1:(0.0004-0.012), the acidic reagent is diluted with the third organic solvent to obtain a third organic solvent containing the acidic reagent.
[0052] The fourth organic solvent and the organoaluminum compound are mixed to prepare a fourth organic solvent containing the organoaluminum compound, wherein the concentration of the organoaluminum compound is 20-30 mmol / L.
[0053] (2) performing a first mixing of the first organic solvent containing the copper nanowires, the second organic solvent containing water, and the third organic solvent containing the acidic reagent, and performing ultrasonic dispersion on the first mixed solution to obtain a first mixed product, wherein the mass volume ratio of the copper nanowires to the water in the first mixed product is (2-9.5)×10 4 mg / mL, and the volume ratio of the water to the acidic reagent is 1:(0.01-0.7).
[0054] (3) The first mixed product is mixed with the fourth organic solvent containing the organoaluminum compound for a second time, wherein the molar ratio of the copper element in the copper nanowires to the aluminum element in the organoaluminum compound is 1:(0.006-0.03). The specific process of the second mixing is: maintaining a constant temperature reflux of 50-80°C for 15-25 hours under stirring to obtain a second mixed product.
[0055] (4) The second mixed product is centrifuged at a speed of 3000-4000 rpm for 3-10 min to obtain a solid product. The solid product is then washed three times with ethanol and then dried at 60-80° C. for 8-12 h to obtain the copper-based composite catalyst.
[0056] In the present invention, the timing and order of the preparation processes of the first organic solvent containing copper nanowires, the second organic solvent containing water, the third organic solvent containing an acidic reagent, and the fourth organic solvent containing an organic aluminum compound are not specifically limited. They only need to be prepared before mixing. Those skilled in the art can select the preparation order and timing as needed.
[0057] In the preparation method provided by the present invention, most of the acetic acid introduced during the preparation of the copper-based composite catalyst will be removed during the centrifugation and washing process, and a small amount of acetic acid will remain in the copper-based composite catalyst. However, the residual acetic acid will not affect the catalytic performance and stability of the copper-based composite catalyst and can therefore be ignored.
[0058] In the present invention, the copper nanowires are prepared by a hydrothermal self-assembly method, which specifically includes the following steps:
[0059] S1. Mixing a copper source, a reducing agent, an auxiliary agent, and a solvent to obtain a precursor solution.
[0060] S2. After sonicating the precursor solution, transfer it to a reactor and perform a hydrothermal reaction at 150-200° C. for 10-20 h to obtain a hydrothermal reaction product.
[0061] S3. The product of the hydrothermal reaction obtained in step S2 is separated and washed to obtain copper nanowires.
[0062] Preferably, the copper source in step S1 includes copper chloride dihydrate.
[0063] Preferably, the reducing agent in step S1 includes glucose.
[0064] Preferably, the auxiliary agent in step S1 includes hexadecylamine.
[0065] Preferably, the solvent in step S1 includes water.
[0066] Preferably, the mass ratio of the copper source to the reducing agent in step S1 is 1:(1-1.5), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.
[0067] Preferably, the mass ratio of the copper source to the auxiliary agent in step S1 is 1:(5-7), for example, 1:5.0, 1:5.2, 1:5.4, 1:5.6, 1:5.8, 1:6.0, 1:6.2, 1:6.4, 1:6.6, 1:6.8 or 1:7.0, etc.
[0068] Preferably, the mass volume ratio of the copper source and the solvent in step S1 is 1 mg:(0.3-1) mL, for example, 1 mg:0.3 mL, 1 mg:0.4 mL, 1 mg:0.5 mL, 1 mg:0.6 mL, 1 mg:0.7 mL, 1 mg:0.8 mL, 1 mg:0.9 mL or 1 mg:1.0 mL, etc.
[0069] Preferably, the mixing time in step S1 is 8-12 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.
[0070] Preferably, the ultrasonication time in step S2 is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min.
[0071] Preferably, the separation method in step S2 includes centrifugation.
[0072] Preferably, during the preparation of the copper nanowires, the centrifugal speed is 5000-7000 rpm, for example, 5000 rpm, 5200 rpm, 5400 rpm, 5600 rpm, 5800 rpm, 6000 rpm, 6200 rpm, 6400 rpm, 6600 rpm, 6800 rpm or 7000 rpm, etc.
[0073] Preferably, in the copper nanowire preparation process, the centrifugation time is 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0074] In the process of preparing the copper nanowires, the present invention adopts high-speed centrifugation, mainly to remove granular copper substances and improve the purity of the copper nanowires.
[0075] Preferably, the washing in step S2 includes a first washing and a second washing.
[0076] Preferably, the first washing reagent includes ethanol and n-hexane.
[0077] Preferably, the volume ratio of ethanol to n-hexane is 1:(0.5-1.5), such as 1:0.5, 1:0.6, 1:0.8, 1:1.0, 1:1.2, 1:1.4 or 1:1.5.
[0078] Preferably, the second washing reagent comprises ethanol.
[0079] In the present invention, the prepared copper nanowires can be first stored in an ethanol solution of polyvinyl pyrrolidone, taken out when in use, and the copper nanowires stored in the mixed solution are centrifugally washed with ethanol.
[0080] In a third aspect, the present invention provides a use of the copper-based composite catalyst according to the first aspect, wherein the copper-based composite catalyst is used in an electrocatalytic carbon dioxide reduction reaction.
[0081] Compared with the prior art, the present invention has at least the following beneficial effects:
[0082] (1) The copper-based composite catalyst with a core-shell structure provided by the present invention is a coating of a hydroxyl aluminum oxide shell on the surface of the copper nanowire core. The hydroxyl aluminum oxide in the shell and the copper nanowire in the core interact with each other through Lewis acid-base to construct a copper-oxygen-aluminum metal interface site on the surface of the core, which can promote the interaction of charge transfer, improve the interaction between the surface copper atoms and the main copper, and at the same time, stabilize the oxidized copper species in the core and avoid the reconstruction of the copper-based catalyst, thereby preventing the self-reduction of the oxidized copper at the cathode and the deactivation of the catalyst during the electrocatalytic carbon dioxide reduction reaction. In addition, the improvement of the stability of the copper-based composite catalyst can enhance the stability of the carbon monoxide intermediate generated during the carbon dioxide reduction reaction, thereby promoting carbon-carbon coupling and improving the catalytic performance of the copper-based composite catalyst.
[0083] (2) The preparation method of the copper-based composite catalyst provided by the present invention comprises mixing copper nanowires with water, an acidic reagent and an organoaluminum compound, wherein the organoaluminum compound is hydrolyzed when in contact with water, and at the same time, the water content and the content of the organoaluminum compound in the mixture are diluted by an organic solvent to regulate the speed of the hydrolysis process, thereby forming a coating shell of a hydroxyl compound of aluminum of a specific composition on the surface of the copper nanowire; the addition of acetic acid can regulate the microstructure of the shell to form a hydroxyl aluminum oxide shell with a mesoporous structure, and the use of a third organic solvent can dilute the content of acetic acid, thereby further optimizing the microstructure of the shell, regulating the crystal structure of the shell and the pore structure of the hydroxyl aluminum oxide shell, and improving the stabilizing effect of the protective layer of the shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0084] Figure 1 This is a low-magnification transmission electron microscope image of the copper-based composite catalyst provided in Example 1.
[0085] Figure 2 This is a high-magnification transmission electron microscope image of the copper-based composite catalyst provided in Example 1.
[0086] Figure 3 This is a comparison chart of the ultraviolet-visible absorption spectra of the core copper nanowires and the copper-based composite catalyst provided in Example 1.
[0087] Figure 4 This is a comparison chart of the infrared absorption spectra of the copper-based composite catalyst provided in Example 1 and the aluminum oxyhydroxide of the shell.
[0088] Figure 5 This is a high-resolution transmission electron microscope image of the copper-based composite catalyst provided in Example 1.
[0089] Figure 6 This is the Auger spectrum of copper in the copper-based composite catalyst provided in Example 1.
[0090] Figure 7 This is a transmission electron microscope image of the copper-based composite catalyst provided in Example 4.
[0091] Figure 8 Performance diagram of the Faradaic efficiency of the products in the electrocatalytic carbon dioxide reduction reaction provided for Application Example 1 and Comparative Application Example 1 as a function of potential.
[0092] Figure 9 Performance diagram of the Faraday efficiency of the carbon dioxide product changing with time in the electrocatalytic carbon dioxide reduction reaction at constant potential provided for Application Example 1 and Comparative Application Example 1.
[0093] Figure 10 Transmission electron micrograph of the copper-based composite catalyst before the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1.
[0094] Figure 11 Transmission electron micrograph of the copper-based composite catalyst after the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1.
[0095] Figure 12 Transmission electron microscopy image of the copper nanowire catalyst before the electrocatalytic carbon dioxide reduction reaction provided in Comparative Application Example 1.
[0096] Figure 13 Transmission electron microscopy image of the copper nanowire catalyst after the electrocatalytic carbon dioxide reduction reaction provided in Comparative Application Example 1.
[0097] Figure 14 The X-ray diffraction patterns of the copper-based composite catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1.
[0098] Figure 15 The X-ray diffraction patterns of the copper nanowire catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Comparative Application Example 1 are shown.
[0099] Figure 16 Electrochemical activity area diagrams of the copper-based composite catalyst and the copper nanowire catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided for Application Example 1 and Comparative Application Example 1, respectively. DETAILED DESCRIPTION
[0100] The technical solution of the present invention will be further described below with reference to the accompanying drawings and through specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0101] The copper nanowires used in the following examples were prepared using the following preparation method, which includes the following steps:
[0102] S1. Add 136 mg of copper chloride dihydrate, 173 mg of dextrose, and 770 mg of hexadecylamine to 60 mL of water and stir for 12 h to obtain a precursor solution.
[0103] S2. The precursor solution obtained in step S1 was ultrasonicated for 20 min, then transferred to a 100 mL polytetrafluoroethylene reactor, heated to 160° C. and reacted for 16 hours to obtain a hydrothermal reaction product.
[0104] S3. The product of the hydrothermal reaction obtained in step S2 was centrifuged at 6000 rpm for 10 min to obtain a solid product. The solid product was then washed three times with a mixed solvent of ethanol and n-hexane in a volume ratio of 1:1, and then washed once with ethanol to obtain copper nanowires.
[0105] Example 1
[0106] This embodiment provides a copper-based composite catalyst, comprising a core and a shell coated on the surface of the core, wherein the core comprises copper nanowires, the shell comprises aluminum oxyhydroxide, the molar ratio of copper in the core to aluminum in the shell is 1:0.029, and the specific surface area of the copper-based composite catalyst is 48.22 m 2 / g.
[0107] The average diameter of the copper nanowires in the core is 46.7 nm, and the average length is 6.3 μm. The copper in the copper nanowires in the core includes divalent copper and monovalent copper, and the molar ratio of divalent copper to monovalent copper is 7.2:2.8.
[0108] The shell has a mesoporous structure with an average pore diameter of 2.6 nm and an average thickness of 4.5 nm.
[0109] This embodiment also provides a method for preparing the copper-based composite catalyst, comprising the following steps:
[0110] (1) The copper nanowires washed twice with ethanol and dried were dispersed in isopropanol at a mass volume ratio of 0.6 mg / mL, and ultrasonically dispersed for 10 minutes to obtain isopropanol containing copper nanowires.
[0111] According to the volume ratio of isopropyl alcohol to deionized water being 1:0.01, deionized water was diluted with isopropyl alcohol to obtain isopropyl alcohol containing water.
[0112] According to the volume ratio of isopropyl alcohol to acetic acid reagent being 1:0.01, the acetic acid reagent having a concentration of 17.4 mol / L was diluted with isopropyl alcohol to obtain isopropyl alcohol containing acetic acid reagent.
[0113] Isopropyl alcohol and aluminum isopropylate are prepared into an isopropyl alcohol solution containing aluminum isopropylate, wherein the concentration of the aluminum isopropylate in the solution is 25 mmol / L.
[0114] (2) adding isopropyl alcohol containing water and isopropyl alcohol containing acetic acid reagent in sequence to the isopropyl alcohol containing copper nanowires, performing a first mixing under ultrasonic conditions, and dispersing the mixed solution by ultrasound to obtain a first mixed product, wherein the mass volume ratio of copper nanowires to water in the first mixed product is 3.6×10 4 mg / mL, and the volume ratio of water to acetic acid was 1:0.53.
[0115] (3) adding an isopropanol solution containing aluminum isopropoxide at a concentration of 25 mmol / L to the first mixed product obtained in step (2) for second mixing, wherein the molar ratio of the copper element in the copper nanowires to the aluminum element in the aluminum isopropoxide is 1:0.029. The specific process of the second mixing is: maintaining a constant temperature reflux of 60° C. for 20 hours under stirring to obtain a second mixed product.
[0116] (4) The second mixed product obtained in step (3) was centrifuged at a speed of 3500 rpm for 5 min to obtain a solid product. The solid product was then washed three times with ethanol and then dried at 80° C. for 8 h to obtain a copper-based composite catalyst.
[0117] Example 2
[0118] This embodiment provides a copper-based composite catalyst, comprising a core and a shell coated on the surface of the core, wherein the core comprises copper nanowires, the shell comprises aluminum oxyhydroxide, the molar ratio of copper in the core to aluminum in the shell is 1:0.01, and the specific surface area of the copper-based composite catalyst is 65.59 m 2 / g.
[0119] The average diameter of the copper nanowires in the core is 46.7 nm, and the average length is 5.7 μm. The copper in the copper nanowires in the core includes divalent copper and monovalent copper, and the molar ratio of divalent copper to monovalent copper is 7.0:3.0.
[0120] The shell has a mesoporous structure with an average pore diameter of 3.5 nm and an average thickness of 2.8 nm.
[0121] This embodiment also provides a method for preparing the copper-based composite catalyst, comprising the following steps:
[0122] (1) The copper nanowires washed twice with ethanol and dried were dispersed in isopropanol at a mass volume ratio of 0.6 mg / mL, and ultrasonically dispersed for 10 minutes to obtain isopropanol containing copper nanowires.
[0123] According to the volume ratio of isopropyl alcohol to deionized water being 1:0.004, deionized water was diluted with isopropyl alcohol to obtain isopropyl alcohol containing water.
[0124] According to the volume ratio of isopropyl alcohol to acetic acid reagent being 1:0.004, the acetic acid reagent having a concentration of 17.4 mol / L was diluted with isopropyl alcohol to obtain isopropyl alcohol containing acetic acid reagent.
[0125] Isopropyl alcohol and aluminum isopropylate are prepared into an isopropyl alcohol solution containing aluminum isopropylate, wherein the concentration of the aluminum isopropylate in the solution is 20 mmol / L.
[0126] (2) adding isopropyl alcohol containing water and isopropyl alcohol containing acetic acid reagent in sequence to the isopropyl alcohol containing copper nanowires, performing a first mixing under ultrasonic conditions, and dispersing the mixed solution by ultrasound to obtain a first mixed product, wherein the mass volume ratio of copper nanowires to water in the first mixed product is 9.4×10 4 mg / mL, and the volume ratio of water to acetic acid was 1:0.3.
[0127] (3) adding an isopropanol solution containing aluminum isopropoxide at a concentration of 20 mmol / L to the first mixed product obtained in step (2) for second mixing, wherein the molar ratio of the copper element in the copper nanowires to the aluminum element in the aluminum isopropoxide is 1:0.01. The specific process of the second mixing is: maintaining a constant temperature reflux of 50° C. for 25 hours under stirring to obtain a second mixed product.
[0128] (4) The second mixed product obtained in step (3) was centrifuged at a speed of 3000 rpm for 10 min to obtain a solid product, which was washed three times with ethanol and then dried at 60° C. for 12 h to obtain a copper-based composite catalyst.
[0129] Example 3
[0130] This embodiment provides a copper-based composite catalyst, comprising a core and a shell coated on the surface of the core, wherein the core comprises copper nanowires, the shell comprises aluminum oxyhydroxide, the molar ratio of copper in the core to aluminum in the shell is 1:0.03, and the specific surface area of the copper-based composite catalyst is 69.6 m 2 / g.
[0131] The average diameter of the copper nanowires in the core is 46.7 nm, and the average length is 6.7 μm. The copper in the copper nanowires in the core includes divalent copper and monovalent copper, and the molar ratio of divalent copper to monovalent copper is 7.4:2.6.
[0132] The shell has a mesoporous structure with an average pore diameter of 2.1 nm and an average thickness of 4.8 nm.
[0133] This embodiment also provides a method for preparing the copper-based composite catalyst, comprising the following steps:
[0134] (1) The copper nanowires washed twice with ethanol and dried were dispersed in isopropanol at a mass volume ratio of 0.6 mg / mL, and ultrasonically dispersed for 10 minutes to obtain isopropanol containing copper nanowires.
[0135] According to the volume ratio of isopropyl alcohol to deionized water being 1:0.012, deionized water was diluted with isopropyl alcohol to obtain isopropyl alcohol containing water.
[0136] According to the volume ratio of isopropyl alcohol to acetic acid reagent being 1:0.012, the acetic acid reagent having a concentration of 17.4 mol / L was diluted with isopropyl alcohol to obtain isopropyl alcohol containing acetic acid reagent.
[0137] Isopropyl alcohol and aluminum isopropylate are prepared into an isopropyl alcohol solution containing aluminum isopropylate, wherein the concentration of the aluminum isopropylate in the solution is 30 mmol / L.
[0138] (2) adding isopropyl alcohol containing water and isopropyl alcohol containing acetic acid reagent in sequence to the isopropyl alcohol containing copper nanowires, performing a first mixing under ultrasonic conditions, and dispersing the mixed solution by ultrasound to obtain a first mixed product, wherein the mass volume ratio of copper nanowires to water in the first mixed product is 3.1×10 4 mg / mL, and the volume ratio of water to acetic acid was 1:0.7.
[0139] (3) adding an isopropanol solution containing aluminum isopropoxide at a concentration of 30 mmol / L to the first mixed product obtained in step (2) for second mixing, wherein the molar ratio of the copper element in the copper nanowires to the aluminum element in the aluminum isopropoxide is 1:0.03. The specific process of the second mixing is: maintaining a constant temperature reflux of 80° C. for 15 hours under stirring to obtain a second mixed product.
[0140] (4) The second mixed product obtained in step (3) was centrifuged at a speed of 4000 rpm for 3 minutes to obtain a solid product. The solid product was then washed three times with ethanol and then dried at 70° C. for 10 hours to obtain a copper-based composite catalyst.
[0141] Example 4
[0142] The only difference between this embodiment and embodiment 1 is that the copper-based composite catalyst provided in this embodiment has a specific surface area of 70.6 m 2 / g, the shell has mesopores with an average pore diameter of 2.6 nm, and the shell has an average thickness of 6.9 nm. Accordingly, in the preparation method of the copper-based composite catalyst provided in this embodiment, the volume ratio of water to acetic acid in the first mixed product is 1:0.26. The remaining contents are the same as in Example 1.
[0143] Example 5
[0144] The only difference between this embodiment and embodiment 1 is that in the preparation method of the copper-based composite catalyst provided in this embodiment, the volume ratio of water to acetic acid in the first mixed product is 1:0.05. The rest of the contents are the same as those in embodiment 1.
[0145] Example 6
[0146] The only difference between this embodiment and embodiment 1 is that in the preparation method of the copper-based composite catalyst provided in this embodiment, the volume ratio of water to acetic acid in the first mixed product is 1:1. The rest of the contents are the same as those in embodiment 1.
[0147] Example 7
[0148] The only difference between this embodiment and embodiment 1 is that in the copper-based composite catalyst provided in this embodiment, the molar ratio of the copper element in the core to the aluminum element in the shell is 1:0.005. The rest of the contents are the same as those in embodiment 1.
[0149] Example 8
[0150] The only difference between this embodiment and embodiment 1 is that in the copper-based composite catalyst provided in this embodiment, the molar ratio of the copper element in the core to the aluminum element in the shell is 1:0.035. The rest of the contents are the same as those in embodiment 1.
[0151] Example 9
[0152] The only difference between this embodiment and Example 1 is that in the preparation method of the copper-based composite catalyst provided in this embodiment, when preparing the isopropyl alcohol containing water and the isopropyl alcohol containing the acetic acid reagent in step (1), the volume ratio of isopropyl alcohol to water is 1:0.001, and the volume ratio of isopropyl alcohol to acetic acid is 1:0.0001. The remaining contents are the same as those in Example 1.
[0153] Example 10
[0154] The only difference between this embodiment and Example 1 is that in the preparation method of the copper-based composite catalyst provided in this embodiment, when preparing the isopropyl alcohol containing water and the isopropyl alcohol containing the acetic acid reagent in step (1), the volume ratio of isopropyl alcohol to water is 1:0.02, and the volume ratio of isopropyl alcohol to acetic acid is 1:0.02. The rest of the contents are the same as in Example 1.
[0155] Example 11
[0156] The only difference between this embodiment and embodiment 1 is that aluminum isopropoxide is replaced by an inorganic aluminum compound AlCl3 having an equal molar amount of aluminum element. The rest of the contents are the same as those in embodiment 1.
[0157] Comparative Example 1
[0158] The only difference between this comparative example and Example 1 is that aluminum oxyhydroxide is omitted and only copper nanowires are used as the catalyst. The rest of the contents are the same as Example 1.
[0159] Application Example 1
[0160] This application example provides an electrocatalytic carbon dioxide reduction reaction, including the following steps:
[0161] (A) The working electrode is located in an area of 0.5 cm 2 0.15 mg of the copper-based composite catalyst provided in Example 1 was loaded on the hydrophobic carbon paper, which was connected to the working electrode clip.
[0162] (B) In a typical two-compartment H-cell reaction cell, a Fumasep FAA-3-PK-75 anion membrane (FuMA-Tech, Germany) was used for separation. The reaction chambers were filled with a 0.1 mol / L potassium bicarbonate aqueous solution. Carbon dioxide was used as the reaction gas. Silver / silver chloride was used as the reference electrode, and a platinum mesh was used as the counter electrode. Testing was performed using an electrochemical workstation (VSP s / n: 2406, Biologic).
[0163] (C) Argon gas is used to remove air from the solution, and carbon dioxide as a reaction gas is introduced into the solution until the solution is saturated with carbon dioxide (saturation concentration is 0.13 mol / L). Electricity is then applied to perform an electrocatalytic carbon dioxide reduction reaction to obtain a product of the electrocatalytic carbon dioxide reduction reaction.
[0164] Application Example 2-11 and Comparative Application Example 1
[0165] The only difference between Application Examples 2-11 and Comparative Application Example 1 and Application Example 1 is that the copper-based composite catalyst provided in Example 2-11 and the copper nanowire catalyst provided in Comparative Example 1 are loaded onto the hydrophobic carbon paper in step (A), respectively. All other details are the same as in Application Example 1.
[0166] The gaseous products of the electrocatalytic carbon dioxide reduction reaction provided in Examples 1-11 and Comparative Application Example 1 were detected by gas phase analysis and quantitatively tested every 120 minutes. The liquid products were detected and quantified using nuclear magnetic resonance spectroscopy. The specific performance tests are as follows:
[0167] (1) Catalyst Performance Stability: The catalyst was tested at a constant potential of -1.1 V relative to the standard hydrogen electrode under continuous flow of carbon dioxide. The product was detected every 2 hours for a total test time of 48 hours. The Faradaic efficiency of the product was plotted over time, and the Faradaic efficiency of the C2 product at 24 hours and 48 hours was recorded. The test results are shown in Table 1.
[0168] (2) Structural stability of the catalyst: The test was carried out under the conditions of a constant potential of -1.1 V relative to the standard hydrogen electrode and continuous flow of carbon dioxide. The catalyst was tested once every 2 hours for a total test time of 48 hours. The changes in the crystal structure of the catalyst used before and after the reaction were detected by transmission electron microscopy and X-ray diffraction spectroscopy. The test results are as follows: Figure 10-15 shown.
[0169] The test results are shown in Table 1.
[0170] Table 1
[0171]
[0172] The test results show that:
[0173] (1) It can be seen from Application Examples 1 to 4 that the copper-based composite catalyst provided by the present invention is coated with a hydroxyaluminum oxide shell on the surface of the copper nanowire core. The hydroxyaluminum oxide in the shell and the copper nanowire in the core interact with the Lewis acid-base to construct a copper-oxygen-aluminum metal interface site on the surface of the core, which can improve the migration energy of the copper atom surface, stabilize the copper species in the core, avoid the reconstruction of the copper-based catalyst, and improve the catalytic performance and stability of the copper-based composite catalyst.
[0174] Figure 1 and Figure 2 This is a transmission electron microscope image of the copper-based composite catalyst prepared in Example 1. Figure 1 and Figure 2 It can be seen that the diameter of the copper-based composite catalyst can reach 55.8 nm, and the average thickness of the aluminum oxyhydroxide shell is 4.5 nm, indicating that aluminum oxyhydroxide is successfully coated on the surface of the copper nanowires.
[0175] Figure 3 The ultraviolet-visible light absorption spectrum of the core copper nanowires and the copper-based composite catalyst provided in Example 1 is obtained by Figure 3 It can be seen that the absorption peak of the copper nanowire coated with aluminum oxyhydroxide shell is red-shifted compared with the original copper nanowire, further indicating that aluminum oxyhydroxide is successfully coated on the surface of the copper nanowire.
[0176] Figure 4 The infrared absorption spectrum of the aluminum oxyhydroxide of the copper-based composite catalyst and the shell provided in Example 1 is Figure 4 It can be seen that the copper-based composite catalyst contains aluminum oxyhydroxide.
[0177] Figure 5 This is a high-resolution transmission electron microscope image of the copper-based composite catalyst provided in Example 1. The lattice of the selected area in the image corresponds to the (130) crystal plane of hydroxyaluminum oxide, i.e., AlO(OH), which means that the composition of the surface shell is determined to be hydroxyaluminum oxide (i.e., AlO(OH)).
[0178] Figure 6 This is an Auger spectrum of copper in the copper-based composite catalyst provided in Example 1. As can be seen from the figure, the copper in the copper-based composite catalyst includes divalent copper and monovalent copper, wherein the molar ratio of divalent copper to monovalent copper is 7.2:2.8.
[0179] Figure 7 This is a transmission electron microscope image of the copper-based composite catalyst provided in Example 4. As can be seen from the image, in the copper-based composite catalyst provided in Example 4, an aluminum oxyhydroxide shell structure is coated on the surface of the copper nanowires.
[0180] (2) By comparing Application Example 1 with Application Examples 5-6, it can be seen that in the preparation method of the copper-based composite catalyst provided by the present invention, if the volume ratio of water to acetic acid in the first mixed product is too high, the pore size of the shell formed will be too large, and an effective barrier cannot be formed, thereby affecting the stability of the catalyst; if the volume ratio of the two is too low, the content of acetic acid added is relatively too high, the pore size of the shell will be too small, and the formed shell will be too dense, affecting mass transfer, thereby resulting in poor selectivity of the copper-based composite catalyst.
[0181] (3) By comparing Application Example 1 with Application Examples 7-8, it can be seen that in the copper-based composite catalyst provided by the present invention, if the molar ratio of the copper element in the core to the aluminum element in the shell is too high, and the relative content of the aluminum element in the shell is low, the shell layer can only be partially formed, which cannot fully protect the structure of the copper nanowires; if the molar ratio of the two is too low, and the relative content of the aluminum element in the shell is high, the shell layer formed will be too thick, affecting the mass transfer of the reactants and thus affecting the performance of the composite catalyst.
[0182] (4) By comparing Application Example 1 with Application Examples 9-10, it can be seen that in the preparation method of the copper-based composite catalyst provided by the present invention, if the amount of isopropanol added during the dilution of water and ethanol with isopropanol is too high, the hydrolysis of aluminum isopropoxide will be slow or a shell layer cannot be formed on the copper nanowires; if the amount of isopropanol added is too low, the hydrolysis rate of aluminum isopropoxide will be too fast during the mixing process, affecting the composition and coating effect of the shell surface. At the same time, if the concentration of acetic acid is too high, the hydrolysis process of aluminum isopropoxide will be slowed down or an overly small pore structure will be formed in the shell, thereby affecting the formation of the shell layer and the exposure of copper activity.
[0183] (5) By comparing Application Example 1 and Application Example 11, it can be seen that in the preparation method of the copper-based composite catalyst provided by the present invention, if the organic aluminum compound of aluminum isopropoxide is replaced by an inorganic aluminum compound, the structure of the copper nanowires will be completely destroyed and the target core-shell structure cannot be formed.
[0184] (6) By comparing Application Example 1 and Comparative Application Example 1, it can be seen that if the surface of the copper nanowires is not coated with a hydroxyaluminum oxide shell, the present invention cannot achieve the technical effects of excellent stability and high selectivity of the catalyst in the electrocatalytic carbon dioxide reduction reaction.
[0185] Figure 8 The performance diagram of the Faraday efficiency of the product in the electrocatalytic carbon dioxide reduction reaction provided for Application Example 1 and Comparative Application Example 1 as a function of potential is shown in FIG. Figure 8It can be seen that compared with Comparative Application Example 1 which uses the copper nanowires of Comparative Example 1 directly as a catalyst, under the catalytic conditions of the copper-based composite catalyst provided in Example 1 in Application Example 1, the Faraday efficiency of the carbon II product first increases and then decreases with increasing potential, and reaches the maximum at a potential of -1.1 V relative to the standard hydrogen electrode, indicating that the copper-based composite catalyst provided in Example 1 is more conducive to improving the selectivity of the carbon II product.
[0186] Figure 9 The performance graphs of the Faraday efficiency of the carbon dioxide product over time for the electrocatalytic carbon dioxide reduction reaction at constant potential provided for Application Example 1 and Comparative Application Example 1 show that under the catalytic conditions of the copper-based composite catalyst provided in Example 1, the Faraday efficiency of the carbon dioxide product at a potential of -1.1V in a neutral electrolyte can be stable for 48 hours, and only slightly decreases starting from 24 hours; while in Comparative Application Example 1, where copper nanowires are used directly as a catalyst, the Faraday efficiency of the carbon dioxide product continues to decrease from 50% to 18%, indicating that the aluminum oxyhydroxide shell can maintain the stability of the catalyst performance.
[0187] Figure 10 and Figure 11 They are transmission electron microscope images of the copper-based composite catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1, Figure 12 and Figure 13 The transmission electron microscope images of the copper nanowire catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Comparative Application Example 1 are shown respectively. Figure 10-13 It can be seen that compared with the copper nanowires used as catalysts in Comparative Application Example 1, the copper-based composite catalyst with a specific structure used in Application Example 1 can basically maintain its original morphology and structure after catalyzing the carbon dioxide reaction at a potential of -1.1 V relative to the standard hydrogen electrode for 24 hours, indicating that the hydroxyaluminum oxide shell plays a vital role in the structural stability of the copper-based composite catalyst.
[0188] Figure 14 and Figure 15 The X-ray diffraction patterns of the copper-based composite catalyst and the copper nanowire catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1 and Comparative Application Example 1 are shown. As can be seen from the figure, after catalyzing the carbon dioxide reaction at a potential of -1.1V relative to the standard hydrogen electrode for 24 hours, the relative intensity of the (111) crystal plane and the (200) crystal plane of the copper-based composite catalyst provided in Example 1 did not change significantly, while the (111) crystal plane and the (200) crystal plane of the copper nanowire catalyst provided in Comparative Example 1 were both destroyed, indicating that the aluminum oxyhydroxide shell can prevent the surface copper atoms from being reconstructed, thereby maintaining the crystal structure of the copper nanowire.
[0189] Figure 16The electrochemical activity area diagrams of the copper-based composite catalyst and the copper nanowire catalyst before and after the electrocatalytic carbon dioxide reduction reaction provided in Application Example 1 and Comparative Application Example 1, respectively, show that before the carbon dioxide electroreduction reaction, the electrochemical activity areas of the copper-based composite catalyst provided in Example 1 and the copper nanowire catalyst provided in Comparative Example 1 are similar. After 48 hours of reaction, the electrochemical activity area of the copper nanowire catalyst increased by 95%, while that of the copper-based composite catalyst only increased by 44.5%, indicating that the aluminum oxyhydroxide shell can effectively prevent the reconstruction of copper atoms on the surface of the copper nanowire by constructing a copper-oxygen-aluminum interface.
[0190] In summary, the copper-based composite catalyst with a core-shell structure provided by the present invention constructs a coating of a hydroxyl aluminum shell on the surface of the copper nanowire core, and the hydroxyl aluminum in the shell and the copper nanowire in the core interact with each other through Lewis acid-base to construct a copper-oxygen-aluminum metal interface site on the surface of the core, which can promote the interaction of charge transfer, improve the migration energy of the copper atom surface, and at the same time, stabilize the oxidized copper species in the core, and avoid the reconstruction of the copper-based catalyst, thereby preventing the self-reduction of oxidized copper at the cathode and the deactivation of the catalyst during the electrocatalytic carbon dioxide reduction reaction. In addition, the improvement of the stability of the copper-based composite catalyst can enhance the stability of the carbon monoxide intermediates generated during the carbon dioxide reduction reaction, thereby promoting carbon-carbon coupling and improving the catalytic performance of the copper-based composite catalyst.
[0191] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A copper-based composite catalyst, characterized in that The copper-based composite catalyst comprises a core and a shell coated on the surface of the core, wherein the core comprises copper nanowires, and the shell comprises aluminum oxyhydroxide.
2. The copper-based composite catalyst according to claim 1, wherein The shell has a mesoporous structure; Preferably, the average pore size of the mesoporous structure in the shell is 2-4 nm; Preferably, the average thickness of the shell is 2-7 nm; Preferably, the specific surface area of the copper-based composite catalyst is 40-80m 2 / g.
3. The copper-based composite catalyst according to claim 1 or 2, characterized in that In the copper-based composite catalyst, the molar ratio of the copper element in the copper nanowires to the aluminum element in the aluminum oxyhydroxide is 1:(0.006-0.03); Preferably, the copper element in the copper nanowires includes divalent copper and monovalent copper; Preferably, the molar ratio of the divalent copper to the monovalent copper is (7-9):(1-3); Preferably, the average diameter of the copper nanowires is 30-70 nm; Preferably, the average length of the copper nanowires is 1-100 μm.
4. A method for preparing a copper-based composite catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: A first organic solvent containing copper nanowires, a second organic solvent containing water, and a third organic solvent containing an acidic reagent are first mixed to obtain a first mixed product; the first mixed product is second mixed with a fourth organic solvent containing an organic aluminum compound, separated, and then dried to obtain the copper-based composite catalyst.
5. The preparation method according to claim 4, characterized in that In the first organic solvent containing copper nanowires, the mass volume ratio of the copper nanowires to the first organic solvent is 0.3-1 mg / mL; Preferably, the preparation process of the first organic solvent containing copper nanowires comprises: dispersing the copper nanowires in the first organic solvent, and subjecting the solvent to ultrasound to obtain the first organic solvent containing copper nanowires; Preferably, the copper nanowires are pretreated before being dispersed in the first organic solvent; Preferably, the pretreatment method includes cleaning.
6. The preparation method according to claim 4 or 5, characterized in that In the second organic solvent containing water, the volume ratio of the second organic solvent to the water is 1:(0.004-0.012); Preferably, the preparation process of the third organic solvent containing the acidic reagent comprises: diluting the acidic reagent with a third organic solvent to obtain the third organic solvent containing the acidic reagent; Preferably, the acidic reagent comprises acetic acid; Preferably, in the third organic solvent containing the acidic reagent, the volume ratio of the third organic solvent to the acidic reagent is 1:(0.0004-0.012); Preferably, in the first mixed product, the mass volume ratio of the copper nanowires to the water is (2-9.5)×10 4 mg / mL; Preferably, in the first mixed product, the volume ratio of the water to the acidic reagent is 1:(0.01-0.7).
7. The preparation method according to any one of claims 4 to 6, characterized in that In the fourth organic solvent containing the organoaluminum compound, the concentration of the organoaluminum compound is 20-30 mmol / L; Preferably, in the second mixing process, the molar ratio of the copper element in the copper nanowires to the aluminum element in the organic aluminum compound is 1:(0.006-0.03).
8. The preparation method according to any one of claims 4 to 7, characterized in that The temperature of the second mixing is 50-80°C; Preferably, the second mixing time is 15-25h; Preferably, the separation method includes centrifugation; Preferably, the centrifugal speed is 3000-4000 rpm; Preferably, the centrifugation time is 3-10 min.
9. The preparation method according to claim 4, characterized in that The preparation method comprises the following steps: (1) dispersing the copper nanowires in a first organic solvent at a mass-to-volume ratio of 0.3-1.0 mg / mL, and subjecting the solvent to ultrasound to obtain a first organic solvent containing the copper nanowires; diluting the water with the second organic solvent according to a volume ratio of the second organic solvent to water of 1:(0.004-0.012) to obtain a second organic solvent containing water; According to the volume ratio of the third organic solvent to the acidic reagent being 1:(0.0004-0.012), the acidic reagent is diluted with the third organic solvent to obtain a third organic solvent containing the acidic reagent; preparing a fourth organic solvent and an organoaluminum compound to form a fourth organic solvent containing an organoaluminum compound, wherein the concentration of the organoaluminum compound is 20-30 mmol / L; (2) performing a first mixing of the first organic solvent containing the copper nanowires, the second organic solvent containing water, and the third organic solvent containing the acidic reagent, and performing ultrasonic dispersion on the first mixed solution to obtain a first mixed product, wherein the mass volume ratio of the copper nanowires to the water in the first mixed product is (2-9.5)×10 4 mg / mL, the volume ratio of the water to the acidic reagent is 1:(0.01-0.7); (3) performing a second mixing of the first mixed product and the fourth organic solvent containing the organoaluminum compound, wherein the molar ratio of the copper element in the copper nanowires to the aluminum element in the organoaluminum compound is 1:(0.006-0.03), and the specific process of the second mixing is: maintaining a constant temperature reflux of 50-80° C. for 15-25 hours under stirring to obtain a second mixed product; (4) The second mixed product is centrifuged at a speed of 3000-4000 rpm for 3-10 min to obtain a solid product. The solid product is then washed three times with ethanol and then dried at 60-80° C. for 8-12 h to obtain the copper-based composite catalyst.
10. Use of the copper-based composite catalyst according to any one of claims 1 to 3, characterized in that: The copper-based composite catalyst is used in electrocatalytic carbon dioxide reduction reaction.
Citation Information
Cited By
Intermittent stop-based copper-based electrocatalyst regeneration method
CN121826798A